Inconvenient truth? How different mentoring approaches impact student–teacher identity development - Prabjandee, Denchai (Frontiers in Education, 2022)
This research attempted to illustrate how different mentoring approaches impact student-teacher identity development. Mentoring approaches in this study were categorized into transmission-oriented and constructivist-oriented. Guided by the biographical-narrative identity theory, the data in this study were extracted from interviews with four student teachers from Thailand while they were in the teaching practicum. It was found that student teachers who received the constructivist-oriented mentoring perceived themselves as teachers, were more confident about their teaching abilities, and expressed willingness to enter the teaching profession than those who received the transmission-oriented mentoring. Implications for selecting qualified school-based mentor teachers and the urgent need to offer an induction program to support mentors are discussed.